Penerapan Intervensi Microwave Diathermy (MWD) dan Scapula Stabilization Exercise Pada Gangguan Gerak dan Fungsi Leher akibat Forward Head Posture (FHP) - BUSTAM, IKA; Andini, Shania (IKesT Muhammadiyah Palembang, 2024)
Background: Forward Head Posture is a body posture depicted with the head facing anteriorly or forward. The main symptom of Forward Head Posture is pain disorders that can affect functional disorders. This case study patient is a 28-year-old man diagnosed with Forward Head Posture. Objective: This case study aims to determine the management and effect of physiotherapy interventions in patients by using Microwave Diathermy (MWD) and Scapula Stabilization exercises on the condition of FHP. Method: Data collection was carried out by evaluating the patient using the Craniovertebral Angle (CVA) to determine the degree of CVA, Occiput Wall Distance (OWD) to determine the distance of C7 to the wall and Neck Disability Index (NDI) to measure the functional activity of the neck. Evaluations were carried out 6 times over 4 weeks. Results: There was an increase in the Craniovertebral angle from a value of 43.20 to 460. A decrease in the distance of the occiput to the wall from a value of 7.4 cm to 6.5 cm. There was an increase in the functional value of the neck, marked by a decrease in the NDI value of 20%. Conclusion: Microwave Diathermy and Scapula Stabilization Exercise physiotherapy interventions can overcome movement and neck function disorders due to Forward Head Posture.